1983
DOI: 10.2118/11922-pa
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Current Hydraulic Fracturing Design and Treatment Technology-Part 2

Abstract: last month (Pages 677-87) with the author's biography. It addressed stimulation optimization concepts, treatment design considerations, reservoir response potential, fracture propagation, and fracturing rock mechanics.Part 2 is devoted to (1) fracturing materials (fluids, additives, propping agents, etc.), (2) material design (fluid rheology, fluid loss, fracture conductivity, etc.), and (3) field methods to obtain data applicable to predicting and analyzing fracturing behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…10,11 Obviously, a more accurate account of C w is necessary. 12 Our investigation of variations in fluid-loss data has shown that the widest variations result from core preparation and fluid mixing procedures.…”
Section: Discussionmentioning
confidence: 96%
“…10,11 Obviously, a more accurate account of C w is necessary. 12 Our investigation of variations in fluid-loss data has shown that the widest variations result from core preparation and fluid mixing procedures.…”
Section: Discussionmentioning
confidence: 96%
“…Hydraulic fracturing involves injecting proppant-laden slurries, for example, the mixture of sand and slickwater, under high pressure down a tubular wellbore and through perforations to initiate and propagate hydraulically-induced fractures (Veatch 1983; Xu and Wong 2013; Zhai et al 2015). The pressure and injected fluid distribution during a hydraulic fracturing treatment along a horizontal well is illustrated schematically in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main objectives in conducting hydraulic fracturing operations is to design a fracture that optimizes fluid flow to the well, without negatively affecting the integrity of the n involve choosing ) the most effective materials (fluids and proppants), (2) the necessary volume of material, (3) the injection rate, and (4) the injection schedule (Veatch, 1983b). In order to effectively identify an optimal fracture design, detailed information about the lithology and fracturing components needs to be utilized.…”
Section: Introductionmentioning
confidence: 99%